Performance scorecards : - Chang, Richard Y. (Jossey-Bass Publishers, 2000)
Base your business decisions on up-to-the-minute "snapshots" of your company's performance. Because they can be customized to track indicators specific to your organization's success, Performance Scorecards are a busy manager's best resource for quickly aligning strategy and promoting behaviors that lead to desired results. Use them to gauge sales, employee satisfaction, quality-whatever factors most influence your company's progress. You'll be able to make better, more informed decisions, guide and manage shifts in business direction, and keep every employee focused on important business goals. Through their fictional account of manager Vince Sharp's use of the scorecards, Chang and Morgan show readers exactly how the process works.